(untitled) (Research, Society and Development, 2020)
No-tillage system in cerrado regions assumes importance due to the fact that it does not turn over the soil, to use cover crops and to recommend crop rotation. The objective of this research was to evaluate the effect of the amount of lime applied during the period, cover crops in the off season and nitrogen doses, in the 2015/16, 2016/2017 and 2017/18 crops in the nutrient leaf content and grain yield of maize. The study began in 2000/01 in an experimental area in the Selvíria, MS, Brazil in Oxisol, where the no-tillage system was initiated. The experimental design used was the randomized blocks with three replications in a factorial arrangement 5x2x3, consisting 5 residual combinations of lime and gypsum association (6.92 (T1), 11.44 (T2), 7.73 (T3), 10. 63(T4) and 0.81(T5) t ha-1, where T3 and T4 received in February/2017, 1.7 t ha-1 of gypsum), 2 cover crops in the off-season (Crotalaria juncea and Pennisetum americanum) and 3 N doses as top dressing (0, 90 and 180 kg ha-1). The residual doses of lime with or without gypsum did not change the grain yield of maize; the increase N doses as top dressing provided an increase in grain yield in the 3 agricultural years of the research, and the maize crop after crotalaria presented lower demand for nitrogen.